THE PARATETHYS AT THE END OF THE EARLY-MIDDLE MIOCENE AND ITS RELATIONS WITH SURROUNDING BASINS - Goncharova I.A.; Shcherba I.G. (My University, 1997)
The Paratethys cyclic development (Andrusov, 1961; Nevesskaya et al., 1986) determined the main trend in investigating the composition and evolution of its biota, its hydrology, paleogeography, and tectonics. Each cycle was marked by changes from marine to semimarine and brackish conditions. Incidentally, each subsequent cycle with marine or semimarine regime became increasingly shorter, while the brackish stage became, on the contrary, progressively longer (Nevesskaya et al., 1986).
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен